USING SHORT STORIES TO IMPROVE STUDENTS’ READING COMPREHENSION AT SENIOR HIGH SCHOOL - Sitti Hajrah; Muliaty Ibrahim; Hasnani; Sujarwo (STKIP Subang, 2025)
Sitti Hajrah, 2025. Using Short Stories to Improve Students' Reading Comprehension at Senior High School (Supervised by Muliaty Ibrahim and Hasnani). This study aims to determine the effect of using short stories on the reading comprehension of tenth-grade students at SMA Negeri 3 Bantaeng in the 2024/2025 academic year: The research employed a quasi-experimental method with a quantitative approach. The sample consisted of two classes: class X6 as the experimental group and class X2 as the control group, selected through purposive sampling. The research instruments included tests and documentation in the form of pre-tests and post-tests, as well as supporting documentation such as photographs. The data were analyzed using descriptive statistics, normality and homogeneity tests, and a n independent sample t-test. The results showed that the average pre-test score of the experimental group was 63.73, which increased to 85.07 in the post-test. In the control group, the average score rose from 67.37 to 76.73. The t-test analysis yielded a significance value of 0.000 < 0.05, indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Hı) was accepted. Therefore, it can be concluded that the use of short stories significantly improves students' reading comprehension.